Spring's arcana - Saintcrow, Lilith (The Dead God's heart ;, 2023)
"Nat Drozdova is desperate to save a life. Doctors can do little for her cancer-ridden mother, who insists there is only one cure--and that Nat must visit a skyscraper in Manhattan to get it. Amid a snow-locked city, inside a sleek glass-walled office, Nat makes her plea and is whisked into a terrifying new world. For the skyscraper holds a hungry winter goddess who has the power to cure her mother...if Nat finds a stolen object of great power. Now Nat must travel with a razor-wielding assassin across an American continent brimming with terror, wonder, and hungry divinities with every reason to consume a young woman. For her ailing mother is indeed suffering no ordinary illness, and Nat Drozdova is no ordinary girl. Blood calls to blood, magic to magic, and a daughter may indeed save what she loves... ...if it doesn't consume her first. This is the way to the Dead God's Heart"--